Profiling the gut structure and microbiota, and identifying two dominant bacteria belonging to the Weissella genus in mandarin fish (Siniperca chuatsi) fed an artificial diet - Wang, Jiayu; Hao, Yaotong; Zhang, Lihan; Gao, Xiaowei; Xu, Yihuan; Wang, Jiangjiang; Hanafiah, Fazhan; Khor, Waiho; Sun, Yanfeng; Wu, Chengbin (Frontiers in Microbiology, 2024)
Mandarin fish (Siniperca chuatsi) fed with an artificial diet is progressively gaining popularity, which is important for reducing product prices and resource consumption. However, food is the decisive factor of intestinal microbes, and the profound effects of change in their feeding habit on intestinal microbes of mandarin fish have not been revealed. In the present study, live bait fish and artificial diet were used to feed mandarin fish for 8 weeks to study the effect of different feeding habits on the histology, microbiota structure and dominant bacteria of gut in mandarin fish. The results indicated that feeding with the artificial diet significantly increased the intestinal villi height and muscular thickness in the hindgut of mandarin fish. In addition, the microbiota results showed that there were significant differences of beta diversity of gut microbiota in mandarin fish fed with different diets. At the genus level, feeding artificial diets significantly increased the abundance of Weissella in the mandarin fish gut. Furthermore, two Weissella bacteria were identified and characterized from the midgut contents of mandarin fish fed with artificial diet. Based on 16S rRNA gene sequencing, nine strains were assigned as Weissella confusa (RM125), and one as Weissella cibaria (SJ548). Biochemical analyses based on the VITEK2 method revealed a pattern of metabolic activities against W. confusa RM125 and W. cibaria SJ548, with 13 positive and 29 negative results, respectively. W. confusa RM125 and W. cibaria SJ548 exhibited sensitivities toward a variety of pathogens, including V. harveyi, S. aureus and V. parahaemolyticus, E. coli, A. hydrophila, S. enterica, V. anguillarum, and V. alginolyticus, indicating potential probiotics. Therefore, our results confirmed that the transformation of feeding habit altered the structure, microbial composition and dominant bacteria in gut of mandarin fish, and provided evidence that Weissella might play a crucial role in the digestion and absorption of artificial diet in mandarin fish.